CO2 emissions and energy performance analysis of ground-source and solar-assisted ground-source heat pumps using low-GWP refrigerants. (15th December 2022) - Lee, Minwoo; Kim, Jinyoung; Shin, Hyun Ho; Cho, Wonhee; Kim, Yongchan
Abstract: The energy consumption and CO2 emissions of heat pump systems can be reduced effectively by adopting an appropriate alternative refrigerant. However, investigation on alternative refrigerants for ground-source heat pump (GSHP) and solar-assisted ground-source heat pump (SGSHP) systems is limited although these systems still use conventional refrigerants. In this study, the life cycle climate performance (LCCP) and primary energy consumption (PEC) for GSHP and SGSHP systems using conventional and alternative refrigerants are compared to those for conventional boiler systems. Experiments are conducted to investigate the heating performance of selected refrigerants. For regions with low CO2 emission conversion factor for electricity ( μ C O 2 . e l e c ), GSHP systems using R1234yf are the most suitable considering the LCCP, owing to its low GWP and high performance. However, SGSHP systems using R134a with a large system size are preferred in regions with high μ C O 2 . e l e c, because system efficiency takes the priority in reducing the LCCP. For PEC, SGSHP systems using R134a are recommended owing to its high efficiency. However, in regions where oil or natural gas is used dominantly, either the system size of SGSHPs should be increased or the primary energy conversion factor of electricity should be reduced to guarantee the benefits of PEC reduction of SGSHP systems. Highlights: Life cycle climate performance and primary energy consumption are evaluated. Boiler, ground-source, and solar-assisted ground-source heat pumps are considered. R134a and R1234yf are suitable for energy and climate performance, respectively. Increasing system size is beneficial in climate performance only in Berlin. Primary energy consumption of electricity should be reduced in Bern and Berlin.